Evaluation of Elite Spring Wheat (Triticum aestivum L.) Genotypes for Yield and Yield Attributing Traits under Irrigated Condition - Bhattarai, Ramji Prasad; Ojha, Bishnu Raj; Thapa, Dhruba Bahadur; Kharel, Raju; Ojha, Ankit; Sapkota, Manoj (International Journal of Applied Sciences and Biotechnology, 2017)
Thirty International Maize and Wheat Improvement Centre (CIMMYT) elite lines and Nepalese commercial wheat varieties were grown at Agriculture and Forestry University, Chitwan in Alpha-lattice design to identify high yielding genotypes, yield attributing parameters and correlations between them. Observations were taken for different morpho-physiological and yield attributing traits i.e., days to booting, heading, anthesis, maturity, flag leaf senescence, flag leaf duration, grain filling duration, plant height, spike length, number of grains per spike, thousand kernel weight, hectoliter weight, grain yield and biomass yield. Significant genotypic differences were observed for all the traits studied indicating considerable amount of variation among genotypes for each character. The mean grain yield was 2148 kg/ha and it ranged from 1000 to 3425 kg/ha. BLOUK#1/4/WHEAR/KUKUNA/3/C80.1/3*BATAVIA//2*WBLL1/5/MUNAL #1 (35th ESWYT138) was the highest grain yielding genotype among all followed by CHIBIA//PRLII/CM65531/3/FISCAL/4/DANPHE#1/5/CHIBIA//PRLII/CM65531/3/SKAUZ/BAV92 (ESWYT 141), Gautam, Vijay and CHYAK1*2/3/HUW234+LR34/PRINIA//PFAU/WEAVER (ESWYT129). Grain yield had significant strong positive correlation with grain filling duration (0.685**), plant height (0.606**), thousand kernel weight (0.675**), biomass yield (0.892**) and hectoliter weight (0.586**). Four clusters were formed by cluster analysis and genotypes were grouped in a particular cluster on the basis of similarity of morpho-physiological traits. So, these genotypes may be exploited for their direct release or as parents in hybridization programmes to develop high yielding wheat varieties.Int. J. Appl. Sci. Biotechnol. Vol 5(2): 194-202